Produção do cuidado ao idoso no cenário da estratégia saúde da família - Santos, Adje Silva (2015)
The theme of the production of elderly care mainstreamed by host and link launches look at the needs of the health system is facing from the perspective and effective increase in the elderly population around the world. It is important that the health system be able to meet, receive, take responsibility for the health needs of this segment, considering their peculiarities, offering a comprehensive care, targeted and equitable. This research aims to analyze the production of elderly care by health professionals and discuss the work process of these professionals in the Family Health Strategy. In this study for the care production analysis were adopted two dimensions, namely: reception and bonding. This is a qualitative study conducted in three Family Health Units (USF) belonging to Feira de Santana - BA, data were collected through semi-structured interviews and systematic observation. The study involved 23 professionals from USF. The method used for data analysis was content analysis, from which were formulated two categories of analysis: 1) health work process: producer of cozy and binding actions? 2) Reception and attachment: meetings, contradictions and singularities to provide care to the elderly. The study results, through the work process and its elements such as object of work, instruments, agents and purposes, the performance of the health care professional of the USF is structured preferably by biologicist logic in favor of physician-centered model, directed production procedures and fragmented practice, which reduces the therapeutic object to the treatment of diseases and the alleviation of symptoms, affecting directly the production of care. The production of care, analyzed from the bond and the host is carried out in a field of practice and contradictory and conflicting speeches, however, gives rise to new ways of welcoming the elderly. Therefore, the professionals expressed different ways to welcome, to meet and to relate to the elderly, revealing the dependence of individual willingness, commitment and subjectivity of each subject to their achievement, which compromises the uniformity of the degree of acceptance and linking population. Thus, the research indicates the need for reflection on the practice and organization of the work process developed in the context of USF, involving professionals, users and managers, in order to find solutions to provide comprehensive care, planned, equitable, with new attitudes, postures and commitments in order to provide comprehensive care, humanized and quality to the elderly, enhanced by warm and actions by prioritizing the use of relational technologies in search of effective production of health care.